Telothelepodidae, Thelepodidae and Trichobranchidae (Annelida, Terebelliformia) from Lizard Island, Great Barrier Reef, Australia - Hutchings, Pat; Nogueira, João Miguel De Matos; Carrerette, Orlemir (Zootaxa, 2015)
In a survey of the polychaetes of the Lizard Island region, six species of polychaetes belonging to the families Telothelepodidae Nogueira, Fitzhugh & Hutchings, 2013, Thelepodidae Hessle, 1917 and Trichobranchidae Malmgren, 1866 were found, from material collected during the Lizard Island Polychaete Taxonomic Workshop, and material collected by previous projects undertaken by the Australian Museum. This material includes one new species of Rhinothelepus Hutchings, 1974 (Telothelepodidae); one new species of each of the genera, Euthelepus McIntosh, 1885, Streblosoma Sars, 1872, and Thelepus Leuckart, 1849 (Thelepodidae); and one new species of Terebellides Sars, 1835 and another of Trichobranchus Malmgren, 1866 (Trichobranchidae). Keys for identification of these species are provided, together with full descriptions for all species, as well as comparisons with the morphologically most similar congeners.